2020
DOI: 10.51791/njap.v44i2.1115
|View full text |Cite
|
Sign up to set email alerts
|

Carcass characteristics of finishing broiler chickens fed varying levels of crude fibre and energy in multi-fibre source-based diets

Abstract: The carcass characteristics of unsexed Obamarshal broiler chickens fed three levels (4, 8 and 12%) of Crude Fibre (CF) and three levels of Metabolisable Energy (ME) at 2600, 2800 and 3000 ME (Kcal/kg) in multi-fibre source-based diets were assessed using a 3x3 factorial design. The nine experimental diets, each for the starter and finisher phases maintained the calorie: protein ratios of 123:1 and 140:1 respectively. Two hundred and sixteen (216) dayold unsexed broiler chicks were allotted at the outset to nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
2
0
0
Order By: Relevance
“…However, the non-significant (P>0.05) difference in AFW, AWG, AFCR, and APER among the dietary treatments may be due to the energy level which were similar in all the treatment groups. This is in agreement with the findings of Salami and Odunsi (2017) who reported that adequate energy level in the diet improve feed intake, protein intake and calories utilization by birds. The proximate energy level of the experimental diets in the present study (3144.86 -3300.11 ME Kcal/kg) is within the energy requirement of broiler finisher as reported by Salami and Odunsi (2017) who opined that dietary energy level of 2800 to 3000 (Kcal/kg) ME has no significant (P>0.05) effect on AWG, FCR and AFW in finisher broiler chickens.…”
Section: The Performance Indices Of Finisher Broiler Chickens Fed Diets Containing Graded Levels Of Euphorbia Heterophylla Leaf Mealsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the non-significant (P>0.05) difference in AFW, AWG, AFCR, and APER among the dietary treatments may be due to the energy level which were similar in all the treatment groups. This is in agreement with the findings of Salami and Odunsi (2017) who reported that adequate energy level in the diet improve feed intake, protein intake and calories utilization by birds. The proximate energy level of the experimental diets in the present study (3144.86 -3300.11 ME Kcal/kg) is within the energy requirement of broiler finisher as reported by Salami and Odunsi (2017) who opined that dietary energy level of 2800 to 3000 (Kcal/kg) ME has no significant (P>0.05) effect on AWG, FCR and AFW in finisher broiler chickens.…”
Section: The Performance Indices Of Finisher Broiler Chickens Fed Diets Containing Graded Levels Of Euphorbia Heterophylla Leaf Mealsupporting
confidence: 93%
“…This is in agreement with the findings of Salami and Odunsi (2017) who reported that adequate energy level in the diet improve feed intake, protein intake and calories utilization by birds. The proximate energy level of the experimental diets in the present study (3144.86 -3300.11 ME Kcal/kg) is within the energy requirement of broiler finisher as reported by Salami and Odunsi (2017) who opined that dietary energy level of 2800 to 3000 (Kcal/kg) ME has no significant (P>0.05) effect on AWG, FCR and AFW in finisher broiler chickens. The researchers found that on like the starter phase, the growth rate of finisher were similar across the energy levels which was partly attributed to better development of the gut resulting in nutrient digestion, absorption and utilization.…”
Section: The Performance Indices Of Finisher Broiler Chickens Fed Diets Containing Graded Levels Of Euphorbia Heterophylla Leaf Mealsupporting
confidence: 93%